Characterization of the creole-rice production system in La Mojana, in Colombia - Cadena Torres, Jorge; Cuello Pérez, Diana Maria; Romero Ferrer, Jorge Luis; Pérez Cantero, Shirley Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2021)
La Mojana is a subregion with landscapes dominated by large bodies of water, interconnected by a network of pipes and swamps. One of the productive systems of greater social importance is that of Creole rice, to which small producers of the peasant economy are dedicated. Given that socio-economic and technical aspects of this system are unknown, a characterization of the system was carried out using the structured survey method that captured social, technical, and economic aspects. The sampling method used was non-probabilistic and the data were analyzed using descriptive statistics, with measures of central tendency and dispersion. The results showed that Creole rice farmers have been engaged in this productive activity for more than 40 years, in small areas of land on the farm. Part of the production is commercialized in local markets and another part is used to feed the family nucleus, which makes it of great importance in food security. Despite the existence of a supply of improved varieties, with higher yields, a good part of the farmers prefers this type of rice for their food because they attribute a better culinary and nutritional quality to it. At least 46 varieties are used for manually planting, with very low inputs of chemical origin. The main technological limitations of the system were identified and the costs and yields were determined, which allowed calculating a unit cost of US $ 0.40 kg-1. The main risk faced by this productive system is the loss of ancestral seeds, which is why the conservation, purification, and scaling of the creole varieties is proposed, to return them to the community and thus contribute to food security.